EXPLORING THE DIGITAL COMPETENCE OF LECTURERS IN HIGHER EDUCATION: A LITERATURE REVIEW - Shofiana, Fahlulia Rahma; Mustaji, Mustaji; Mariono, Andi; Arianto, Fajar (Paedagoria : Jurnal Kajian, Penelitian dan Pengembangan Kependidikan, 2024)
Abstract: Digital transformation demands the integration of information and communication technology tools in education. This condition is supported by the dominance of current students who are digital native generation. Although the use of technology is not new in higher education, the fact that lecturers are digital immigrants makes it difficult to integrate ICT into the lecture process, while one of the main responsibilities of higher education institutions is to facilitate students with quality learning and competent lecturers to prepare their future. This study aims to explore the level of digital competence of lecturers in higher education, the relationship, factors and efforts to improve it. The method used is a literature review with a narrative approach where the synthesised literature is international journal articles published in the 2020-2024 timeframe. The results showed 1) Digital competence is involved in ICT-integrated lectures from planning to evaluation of learning and reflective practice. 2) Lecturers with high digital competence can evaluate the quality of learning and influence student interest. 3) Age, gender, adaptability, type of institution, domicile location are significant factors of lecturers' digital competence, 4) Efforts that can be made to improve digital competence are: training, providing resource materials, reflective practice, long-term professional support, and incorporating digital competency lectures into prospective lecturer education programmes.Abstrak: Transformasi digital menuntut integrasi perangkat teknologi informasi dan komunikasi (TIK) dalam pendidikan. Kondisi ini didukung dengan dominasi mahasiswa saat ini yang merupakan generasi digital native. Meski penggunaan teknologi bukan hal yang baru di perguruan tinggi namun fakta bahwa dosen merupakan generasi digital imgirant mengakibatkan sulitnya pengintegrasian TIK kedalam proses perkuliahan, sementara salah satu tanggung jawab utama lembaga pendidikan tinggi adalah memfasilitasi mahasiswa dengan pembelajaran berkualitas dan dosen yang kompeten untuk mempersiapkan masa depan mereka. Penelitian ini bertujuan untuk mengeksplorasi tingkat kompetensi digital dosen di perguruan tinggi, hubungan, faktor dan upaya peningkatannya. Metode yang digunakan adalah literature review dengan pendekatan naratif dimana literatur yang disintesiskan adalah artikel jurnal internasional yang diterbitkan dalam rentang waktu 2020-2024. Hasil penelitian menunjukkan 1) Kompetensi digital terlibat dalam perkuliahan terintegrasi TIK dari perencanaan sampai evaluasi pembelajaran dan praktik refektif. 2) Dosen dengan kompetensi digital yang tinggi dapat mengevaluasi kualitas pembelajaran dan mempengaruhi minat mahasiswa. 3) Usia, gender, kemampuan beradaptasi, jenis institusi, lokasi domisili menjadi faktor signifikan kompetensi digital dosen, 4) Upaya yang dapat dilakukan untuk meningkatkan kompetensi digital yaitu: pelatihan, menyediakan sumber materi, praktik reflektif, dukungan profesional jangka panjang, dan memasukkan perkuliahan kompetensi digital ke dalam program pendidikan calon dosen.